2019
DOI: 10.3389/fnbeh.2019.00192
|View full text |Cite
|
Sign up to set email alerts
|

The Predictive Value of Impulsivity and Risk-Taking Measures for Substance Use in Substance Dependent Offenders

Abstract: Impulsivity and risk-taking are known to have an important impact on problematic substance use and criminal behavior. This study examined the predictive value of baseline self-report and behavioral impulsivity and risk-taking measures [Delay Discounting Task (DDT), Balloon Analogue Risk Task (BART) and Behavioral Inhibition, Behavioral Activation Scale (BIS/BAS)] in 12-months follow-up substance use outcomes (e.g., use of alcohol, cannabis and other substances) and criminal recidivism (yes/no). Participants we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 75 publications
(113 reference statements)
0
10
0
1
Order By: Relevance
“… King et al (2014) reviewed the associations between impulsivity and alcohol consumption and observed discrepancies among studies that involved the BART. Some studies showed the BART to predict impulsivity related to alcohol abuse ( Fernie et al, 2010 ; Rose et al, 2014 ) or to be unrelated with impulsivity ( Skeel et al, 2008 ; Rieser et al, 2019 ). Moreover, DeMartini et al (2014) found BART scores to correlate positively with the quantity of alcohol consumption but negatively with the frequency of alcohol consumption, while Ashenhurst et al (2011) found that higher BART scores negatively correlate with alcohol-related symptoms but are unrelated to alcohol use.…”
Section: Discussionmentioning
confidence: 99%
“… King et al (2014) reviewed the associations between impulsivity and alcohol consumption and observed discrepancies among studies that involved the BART. Some studies showed the BART to predict impulsivity related to alcohol abuse ( Fernie et al, 2010 ; Rose et al, 2014 ) or to be unrelated with impulsivity ( Skeel et al, 2008 ; Rieser et al, 2019 ). Moreover, DeMartini et al (2014) found BART scores to correlate positively with the quantity of alcohol consumption but negatively with the frequency of alcohol consumption, while Ashenhurst et al (2011) found that higher BART scores negatively correlate with alcohol-related symptoms but are unrelated to alcohol use.…”
Section: Discussionmentioning
confidence: 99%
“…King and colleagues (2014) reviewed the associations between impulsivity and alcohol consumption and observed discrepancies among studies that involved the BART. Some studies showed the BART to predict impulsivity related to alcohol abuse (Fernie et al, 2010;Rose et al, 2014) or to be unrelated with impulsivity (Skeel et al, 2008;Rieser et al, 2019). Moreover, DeMartini et al (2014 found BART scores to correlate positively with the quantity of alcohol consumption but negatively with the frequency of alcohol consumption, while Ashenhurst et al (2011) found that higher BART scores negatively correlate with alcohol-related symptoms but are unrelated to alcohol use.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal impulsivity may also promote antisocial behaviors, like vandalism, theft, aggression (11)(12)(13)(14)(15), and violence (16). Therefore, impulsivity is generally assessed in criminals [see, for instance, (17)(18)(19)(20)] in order to provide them with an adequate forensic evaluation as well as suitable treatment planning and management (17). Violent offenders usually obtain higher impulsivity scores as compared to subjects convicted for non-violent crimes (21); additionally, greater impulsivity is often associated with higher rates of recidivism (22)(23)(24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%